Validation of the Undesirable Behavior Strategies Questionnaire: Physical Educators' Strategies within the Classroom Ecology - Roka Athina; Dania Aspasia; Stavrou Nektarios; Digelidis Nikolaos (De Gruyter, 2024)
This study sought to propose the Undesirable Behavior Strategies Questionnaire - Physical Education (UBSQ-PE), based on Doyle, W. (1977). Paradigms for research on teacher effectiveness. Review of Research in Education, 5(1), 163-198. classroom ecology paradigm, and validate its use within Physical Education. 289 physical educators participated in the study (80 of them in the pilot study) and completed a survey evaluating the strategies they used across the classroom ecology task systems. An exploratory factor analysis proposed a four-factor solution that measured teachers' strategies for Differentiation of Instruction, Interaction for Students, Classroom Management, and Interaction with Students and explained a cumulative 47.45% of the total explained variance (KMO = 0.809, χ2312{χ }_{231}^{2} = 1,266, 684, p < 0.001). A confirmatory factor analysis indicated a good fit of the data to the four-factor solution (χ2/df ratio = 1.52, comparative fit index = 0.906, Tucker Lewis index = 0.890, standardized root mean square residual = 0.079, root mean square error of approximation = 0.05), providing evidence for the instrument's internal consistency. Multiple analyses of variance showed that there were differences in teachers' strategies based on their gender, age, studies, professional knowledge, and school level. The use of UBSQ-PE asserts that teachers use undesirable behavior (UB) strategies according to their personal and professional characteristics. Teacher education programs could use this information for supporting PE teachers to adjust their UB strategies in response to each classroom's interrelated task systems.